Human errors and factors that influence patient safety in the pre-hospital emergency care setting: Perspectives of South African emergency care practitioners - Mugsien Rowland; Anthonio Adefuye (AOSIS, 2022)
Background: Delivering pre-hospital emergency care has the potential to be hazardous. Despite this, little is known about the factors that precipitate human errors and influence patient safety in the pre-hospital care setting, in contrast to in-hospital care. Similarly, limited report on patient safety and human error issues in the pre-hospital emergency care setting exist in South Africa. Aim: This study investigated the perspectives of emergency care personnel (ECP) in South Africa on the types of human errors and factors that precipitate human errors that influence patient safety in the pre-hospital emergency care setting in South Africa. Setting: This study was conducted in the pre-hospital emergency care environment in South Africa. Methods: This research was designed as an exploratory study that made use of a semi-structured questionnaire administered to 2,000 emergency care personnel. Results: A response rate of 76% was obtained. According to the participants, errors relating to poor judgement, poor skill or knowledge, fatigue, and communication, and individual error are common during pre-hospital care. Inadequate equipment, environmental factors, and personal safety concerns were reported as some of the factors that influence patient safety in the pre-hospital emergency care setting. Conclusion: Implementation of strategies that enhances education and training, clinical skill development, teamwork skills, fatigue management, and leadership skills can help prevent some of the errors identified in this study. Contribution: This study identifies the types of human errors, and factors that precipitate human errors that influence patient safety in the pre-hospital emergency care setting in South Africa.